EFFECT OF PENSION FUNDS, ASSET SIZE AND RETURN ON ASSETS OF INVESTMENT PORTFOLIO PENSION FUND IN INDONBSIA - Didy Handoko (Business and Entrepreneurial Review, 2015)
The background is this research is to explore and get an understanding about the factor that affect the invesment portfolio of pension fund in Indonesia. This research using type of pension fund and size of asset as independent variable. The pension benefit is one of the most important benefits for employee when they get retired. But in the other side it is important for employer and pension fund to improve invesment portfolio in capital market. Sampled used inthis research consisted on 20 pensions fund. Which were observed cross section ally using data of period 2004 and 2008. This researc using multiple regression method for analyzes variables. The result of investigation showed that two independent variable namely type of pension fund and size of asset are influence significantly on investment portfolio and simultaneously all independent variable influence significantly on invesment portfolio of pension fund.